2004
DOI: 10.1126/science.1101485
|View full text |Cite
|
Sign up to set email alerts
|

The 1.2-Megabase Genome Sequence of Mimivirus

Abstract: We recently reported the discovery and preliminary characterization of Mimivirus, the largest known virus, with a 400-nanometer particle size comparable to mycoplasma. Mimivirus is a double-stranded DNA virus growing in amoebae. We now present its 1,181,404-base pair genome sequence, consisting of 1262 putative open reading frames, 10% of which exhibit a similarity to proteins of known functions. In addition to exceptional genome size, Mimivirus exhibits many features that distinguish it from other nucleocytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,097
1
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 934 publications
(1,137 citation statements)
references
References 32 publications
24
1,097
1
15
Order By: Relevance
“…Yet, currently available methods have potential limitations. For example, ssDNA and RNA viruses [11,42] and giant viruses [38] are under-counted when estimates are made via epiflourescence microscopy with standard DNA based stains. Likewise, virus-like particles may not always necessarily represent viruses, and total abundance estimates could include contributions from gene-transfer agents .…”
Section: G Outlier Identificationmentioning
confidence: 99%
“…Yet, currently available methods have potential limitations. For example, ssDNA and RNA viruses [11,42] and giant viruses [38] are under-counted when estimates are made via epiflourescence microscopy with standard DNA based stains. Likewise, virus-like particles may not always necessarily represent viruses, and total abundance estimates could include contributions from gene-transfer agents .…”
Section: G Outlier Identificationmentioning
confidence: 99%
“…Phylogenetic analysis has placed this virus at the end of an independent branch, deeply rooted close to the origin of eukaryotes and most likely representing a distinct domain of life [15]. Our analysis suggested affinity of the mimivirus NATs to those of protists (Figs.…”
Section: Nats In Protists and Associated Large Dna Virusesmentioning
confidence: 65%
“…In particular, this result motivated the proposal that the lineage formed by Mimivirus and its NCLDV relatives might have contributed DNA processing genes to the ancestral eukaryote [7]. However, a subsequent re-analysis of the dataset used in [6] indicated that the position of Mimivirus was an artifact: the genes that were concatenated to build the phylogeny had been acquired by horizontal transfer (HGT) from different sources, resulting in an inconsistent phylogenetic signal that placed them as the outgroup to Eukaryotes [8]. Further analyses demonstrated that NCLDVs have obtained many genes by horizontal transfer from across the three cellular domains [9], [10].…”
Section: Introductionmentioning
confidence: 88%
“…More practically, the small genomes of viruses did not contain enough information to reliably position them on the tree of life [4]. The latter argument was weakened by the discovery of Mimivirus, a nucleocytoplasmic large DNA virus (NCLDV) with a genome of unprecedented size (1.2Mb) and coding capacity ( 1,000 ORFs), exceeding that of many cellular organisms [5], [6]. In an initial phylogenetic analysis, Mimivirus emerged from the branch joining Archaea and Eukaryotes, suggesting that it might represent a distinct fourth domain of life [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation